2022
DOI: 10.1371/journal.pone.0270684
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and hesitancy towards COVID-19 vaccine among university students of Bangladesh

Abstract: Global vaccination coverage is an urgent need to recover the recent pandemic COVID-19. However, people are concerned about the safety and efficacy of this vaccination program. Thus, it has become crucial to examine the knowledge, attitude, and hesitancy towards the vaccine. An online cross-sectional survey was conducted among university students of Bangladesh. Total of 449 university students participated. Most of these students used the internet (34.74%), social media (33.41%), and electronic media (25.61%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 38 publications
7
26
0
Order By: Relevance
“…Nevertheless, for the items with incorrect answers, NP students, >84%, answered otherwise, e.g., antibiotics can be alternatives to vaccines, no need to follow personal protective measures, and the post-vaccination chances of auto-immune disease. Yet, a certain number of pharmacy students also responded incorrectly to knowledge items, possibly due to the inability of the students to cross-verify information when social media information is the major source, corroborating several previous reports [ 4 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Nevertheless, for the items with incorrect answers, NP students, >84%, answered otherwise, e.g., antibiotics can be alternatives to vaccines, no need to follow personal protective measures, and the post-vaccination chances of auto-immune disease. Yet, a certain number of pharmacy students also responded incorrectly to knowledge items, possibly due to the inability of the students to cross-verify information when social media information is the major source, corroborating several previous reports [ 4 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 86%
“…The knowledge-based misconceptions were higher among NP students, e.g., the dose requirements, impact of vaccines on the spread and even cure of the disease, and the chances of auto-immune disease with vaccination. Similar to these findings, a study from Pakistan demonstrated better knowledge among those acquiring medical education [ 26 ], a study from Bangladesh showed positive knowledge among 58.13% of university students [ 29 ], and 42.4% of university students in the UAE demonstrated good knowledge about COVID-19 vaccine [ 4 ]. Nevertheless, for the items with incorrect answers, NP students, >84%, answered otherwise, e.g., antibiotics can be alternatives to vaccines, no need to follow personal protective measures, and the post-vaccination chances of auto-immune disease.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, due to space limitations, vaccine hesitancy and confidence were each captured using one item, which raises concerns of the items' validity and reliability. Finally, not all independent variables were accounted for, including medical mistrust [49], vaccine knowledge [50], and specific social media platforms used [11]. We also did not assess whether participants had received any doses of the COVID-19 vaccine previously.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Over 200 countries have already felt the devastation of a pandemic [ 6 ]. This contagion has developed into a long-term catastrophe, wreaking havoc on society, economies, psychological well-being, and governance [ 1 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%